Applying microbial biostimulants and drought-tolerant genotypes to enhance barley growth and yield under drought stress - Ferioun, Mohamed; Zouitane, Ilham; Bouhraoua, Said; Elouattassi, Yasmine; Belahcen, Douae; Errabbani, Abdellatif; Louahlia, Said; Sayyed, Riyaz; El Ghachtouli, Naïma (Frontiers in Plant Science, 2025)
With climate change, the frequency of regions experiencing water scarcity is increasing annually, posing a significant challenge to crop yield. Barley, a staple crop consumed and cultivated globally, is particularly susceptible to the detrimental effects of drought stress, leading to reduced yield production. Water scarcity adversely affects multiple aspects of barley growth, including seed germination, biomass production, shoot and root characteristics, water and osmotic status, photosynthesis, and induces oxidative stress, resulting in considerable losses in grain yield and its components. In this context, the present review aims to underscore the importance of selecting drought-tolerant barley genotypes and utilizing bio-inoculants constructed from beneficial microorganisms as an agroecological approach to enhance barley growth and production resilience under varying environmental conditions. Selecting barley genotypes with robust physiological and agronomic tolerance can mitigate losses under diverse environmental conditions. Plant Growth Promoting Rhizobacteria (PGPR) play a crucial role in promoting plant growth through nutrient solubilization, nitrogen fixation, phytohormone production, exopolysaccharide secretion, enzyme activity enhancement, and many other mechanisms. Applying drought-tolerant genotypes with bio-inoculants containing PGPR, improves barley's drought tolerance thereby minimizing losses caused by water scarcity.